Analysis of Practical Design for Making Natural Acid-Base Indicator Paper from Purple Golden Flower Extract (Ruellia simplex) as Teaching Material for Acid-Base Material - Muharromah, Hafida Puspita; Fikroh*, Retno Aliyatul; Hermanto, Nur Aziani Binti (Jurnal IPA & Pembelajaran IPA, 2023)
Experiments are an essential part of chemistry. An indicator in the form of a synthetic indicator is generally used in acid-base practice. Using synthetic indicators can cause waste that is dangerous for the environment and is relatively expensive. Purple golden flowers are one of the plants that contain high levels of anthocyanin compounds, which have the potential to be an alternative in making natural acid-base indicators. This research aims to determine the curriculum and learning outcomes of acid-base material, the potential of natural indicator paper for purple golden flowers as a substitute for synthetic indicators, and the feasibility of indicator paper as a design for chemical experiments in SMA/MA. This research uses descriptive qualitative methods, which include literature studies, interviews, observations, and experiments. The purple golden flower indicator is produced by extraction using the maceration method using 96% ethanol solvent. The research results show that paper from purple golden flower extract can be used as a natural acid-base indicator by producing a pink color change in acidic solutions and a green color in essential solutions. Based on the natural indicator paper analysis, the purple golden flower can be used as an alternative indicator in practicum design in schools